Clinical safety and wear resistance of the phospholipid polymer‐grafted highly cross‐linked polyethylene liner. Issue 9 (18th November 2016) - Moro, Toru; Takatori, Yoshio; Tanaka, Sakae; Ishihara, Kazuhiko; Oda, Hiromi; Kim, Yoon Taek; Umeyama, Takashige; Fukatani, Eisei; Ito, Hideya; Kyomoto, Masayuki; Oshima, Hirofumi; Tanaka, Takeyuki; et al.
ABSTRACT: To reduce the production of wear particles and subsequent aseptic loosening, we created a human articular cartilage‐mimicked surface for a highly cross‐linked polyethylene liner, whose surface grafted layer consisted of a biocompatible phospholipid polymer, poly(2‐methacryloyloxyethyl phosphorylcholine). Although our previous in vitro findings showed that poly(2‐methacryloyloxyethyl phosphorylcholine)‐grafted particles were biologically inert and caused no subsequent bone resorptive responses, and poly(2‐methacryloyloxyethyl phosphorylcholine) grafting markedly decreased wear in hip joint simulator tests, the clinical safety, and in vivo wear resistance of poly(2‐methacryloyloxyethyl phosphorylcholine)‐grafted highly cross‐linked polyethylene liners remained open to question. Therefore, in the present study, we evaluated clinical and radiographic outcomes of poly(2‐methacryloyloxyethyl phosphorylcholine)‐grafted highly cross‐linked polyethylene liners 5 years subsequent to total hip replacement in 68 consecutive patients. No reoperation was required for any reason, and no adverse events were associated with the implanted liners. The average Harris Hip Score increased from 38.6 preoperatively to 96.5 5 years postoperatively, and health‐related quality of life, as indicated by the Short Form 36 Health Survey, improved. Radiographic analyses showed no periprosthetic osteolysis or implant migration. Between 1 and 5 years postoperatively, the mean steady‐state wear rate was 0.002 mm/year, which represented a marked reduction relative to other highly cross‐linked polyethylene liners, and appeared to be unaffected by patient‐related or surgical factors. Although longer follow up is required, poly(2‐methacryloyloxyethyl phosphorylcholine)‐grafted highly cross‐linked polyethylene liners improved mid‐term clinical outcomes. The clinical safety and wear‐resistance results are encouraging with respect to the improvement of long‐term clinical outcomes with poly(2‐methacryloyloxyethyl phosphorylcholine)‐grafted highly cross‐linked polyethylene liners. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2007–2016, 2017.